Sex steroids exert a suppressive effect on innate and cell mediated immune responses in fresh water teleost, Channa punctatus. (November 2019) - Patel, Sunita; Choudhary, Meghmala; Chandra, Rakesh Kumar; Bhardwaj, Ajay Kumar; Tripathi, Manish Kumar
Abstract: The main objective of this study was to evaluate the potential role of two important sex steroids, crucial for reproductive success, on innate and cell mediated immune responses in a seasonally breeding, economically important fish, Channa punctatus . Intraperitoneal injections of testosterone and progesterone were given to different groups of fishes. Spleen and head kidney macrophages were isolated and studied for phagocytosis. Superoxide production and nitrite release by phagocytes were also investigated. Cell mediated immunity was measured by lymphocyte proliferation in presence of T and B cell mitogens. In vitro effect of steroids on mitogen induced lymphocyte proliferation was also analyzed. Results of the present investigation revealed the suppressive effects of testosterone and progesterone on immune responses of cells from spleen and head kidney. Concentration dependent effect of sex steroids were observed in vitro studies where phagocytosis and lymphocyte proliferation were suppressed. Immunosupression by these hormones may be the cost of reproduction and it is postulated that by suppressing immune responses, these steroids may, therefore, act as a physiological check regulating the relative amount of energy invested into either reproductive effort or immunocompetence. Highlights: Present study revealed the inhibitory effects of sex steroids on innate and cell mediated immune responses. Differential activity of testosterone was found, where phagocytosis decreased but phagocytic index was unaltered. Sex steroids acted to regulate.